2020
DOI: 10.1111/tpj.14909
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a carotenogenic gene allows faster biomass production by redesigning plant architecture and improving photosynthetic efficiency in tobacco

Abstract: SUMMARY Because carotenoids act as accessory pigments in photosynthesis, play a key photoprotective role and are of major nutritional importance, carotenogenesis has been a target for crop improvement. Although carotenoids are important precursors of phytohormones, previous genetic manipulations reported little if any effects on biomass production and plant development, but resulted in specific modifications in carotenoid content. Unexpectedly, the expression of the carrot lycopene β‐cyclase (DcLCYB1) in Nicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 102 publications
6
73
0
Order By: Relevance
“…Recently, a major growth advantage was reported in tobacco lines expressing the carrot DcLCYB1 (Moreno et al, 2016). This was shown under fully controlled (constant and fluctuating light regimes) and non-controlled climate conditions (Moreno et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a major growth advantage was reported in tobacco lines expressing the carrot DcLCYB1 (Moreno et al, 2016). This was shown under fully controlled (constant and fluctuating light regimes) and non-controlled climate conditions (Moreno et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, induction of leaf senescence was delayed, and mature leaves maintained a high photosynthetic capacity. This ultimately resulted in higher fitness and yield in these tobacco lines (Moreno et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA is also necessary to generate and coordinate the plant’s response against abiotic and biotic stress factors (i.e., drought, salt and pathogens) through synergistic and antagonistic interactions with other hormones (i.e., gibberellins, ethylene and auxins) (De Vleesschauwer et al ., 2010). A recent study showed that enhanced ABA and gibberellin content accumulation through the expression of the Daucus carota (carrot) LYCOPENE β ‐CYCLASE1 ( DcLCYb1 ) leads to increased plant yield and enhanced photosynthetic efficiency in tobacco (Moreno et al ., 2020). ABA‐mediated coordination of the ripening process determines the harvest‐time and shelf‐life of horticulturally important crop plants.…”
Section: Aba Functions and Biosynthesismentioning
confidence: 99%
“…Until now, it was unclear what caused the accelerated development and increased biomass yield in these transgenic tobacco plants. With the support of his current boss, Aleksandra Skirycz, Moreno and his colleagues report in this issue of The Plant Journal that the observed phenotype is mainly caused by altered gibberellin (GA) and abscisic acid (ABA) content (Figure; Moreno et al , 2020). They showed that the ratio of these two hormones was especially important.…”
Section: Figurementioning
confidence: 99%